Quantifying patient spontaneous breathing effort using model-based methods. (August 2021) - Kim, Kyeong Tae; Knopp, Jennifer; Chase, J. Geoffrey
Highlights: NAVA is invasive method to account for spontaneous breathing effort. Model-based dynamic lung elastance is utilised to capture spontaneous breathing effort. Unique and non-invasive method to capture patient effort. Abstract: Background: Spontaneous breathing (SB) effort is common in invasively ventilated patients, as they recover or at low sedation levels. SB effort makes estimation of patient-specific lung mechanics difficult as it introduces unknown inputs. Currently, there is no proven, non-invasive method to quantify SB effort. This study develops non-invasive model-based metrics for SB. Methods: Lung mechanics are identified using a proven model to identify time-varying elastance over inspiration using retrospective data from 22 patients on neutrally adjusted ventilatory assist (NAVA) ventilation. Two methods are explored to quantify negative elastance values associated with breathing effort: a zero-crossing and a trapezoidal method. Area under the resulting positive and negative portions of the time-varying elastance curve is used to quantify SB. Results: The median [interquartile range (IQR)] of AUC quantification of SB for the zero crossing method was −3.29 [−4.80 to −2.50] cmH2O/l, and −1.90 [−2.36 to −1.66] cmH2O/l for the trapezoidal method. AUC values between the two methods were highly correlated, indicating consistency of both model-based methods to quantify SB. Conclusion: Two model-based methods for SB quantification provide consistent metrics for SB. These methods provide computationally simple and cost effective methods to estimate SB effort, which may have clinical value in assessing patient-ventilator synchrony, choice of ventilation mode, or need for weaning.